Endothelial Dysfunction of Patients with Peripheral Arterial Disease Measured by Peripheral Arterial Tonometry. (18th October 2016) - Igari, Kimihiro; Kudo, Toshifumi; Toyofuku, Takahiro; Inoue, Yoshinori
Abstract : Objective . Endothelial dysfunction plays a key role in atherosclerotic disease. Several methods have been reported to be useful for evaluating the endothelial dysfunction, and we investigated the endothelial dysfunction in patients with peripheral arterial disease (PAD) using peripheral arterial tonometry (PAT) test in this study. Furthermore, we examined the factors significantly correlated with PAT test. Methods . We performed PAT tests in 67 patients with PAD. In addition, we recorded the patients' demographics, including comorbidities, and hemodynamical status, such as ankle brachial pressure index (ABI). Results . In a univariate analysis, the ABI value (r = 0.271, P = 0.029 ) and a history of cerebrovascular disease (r = 0.208, P = 0.143 ) were found to significantly correlate with PAT test, which calculated the reactive hyperemia index (RHI). In a multivariate analysis, only the ABI value significantly and independently correlated with RHI (β = 0.254, P = 0.041 ). Conclusion . This study showed a significant correlation between RHI and ABI. The PAT test is a useful tool for evaluating not only endothelial dysfunction but also the hemodynamical state in patients with PAD.